Fuzzy-Based Path Analysis - Khalifa, Othman Omran; Htike@Muhammad Yusof, Zaw Zaw; Khan, Imran Moez (2009)
Video surveillance can be a very powerful tool in the fight against crime, by accurately monitoring human activities. Nevertheless, most surveillance systems today provide only a passive form of site monitoring. Extensive video records may be kept to help find the instigator of criminal activities after the crime has been committed but preventive measures usually require human involvement. In addition to this, there is a need for a large amounts of data storage to keep up to several terabytes of video streams that may be needed for later analysis.